Evaluasi Layanan Digilib Universitas Amikom Purwokerto Menggunakan Framework Itil V3 Domain Service Operation - Ifan Dwi Ramadan; Tegar Romadhany; Julio Yoga Pratama; Rafli Triofansyah; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to evaluate the performance of Digilib services at Amikom University Purwokerto using the Information Technology Infrastructure Library (ITIL) version 3 framework in the Service Operation domain. The phenomenon underlying this study is the indication of a decline in the operational effectiveness of Digilib services as seen from the inconsistency of system performance, access speed, and limited service features. This study uses an evaluative quantitative approach by collecting data through a questionnaire compiled based on five main processes in the Service Operation domain, namely Event Management, Incident Management, Request Fulfillment, Problem Management, and Access Management. The research respondents were library staff directly involved in the management and operation of Digilib services. Data were analyzed using a process maturity model (Process Maturity Model) to assess service capabilities based on a scale of 0–5. The results of the analysis indicate that the overall maturity level of Digilib services is at Level 4 (Managed Process), with an average value of 4.07. This indicates that the operational process has been controlled and measured through certain performance indicators, although there are still opportunities for improvement towards Level 5 (Optimized), especially in the Request Fulfillment and Problem Management domains. These findings contribute to strengthening IT service governance in the higher education sector and provide strategic recommendations for improving automation, system integration, and data-driven service management. The implications of this research encourage the development of policies to improve the quality of digital services and serve as a reference for further research on ITIL implementation in academic settings.